2009
DOI: 10.1007/s11295-009-0256-3
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetic structure of Betula maximowicziana in the Chichibu mountain range, central Japan

Abstract: We evaluated the genetic structure of 16 Betula maximowicziana populations in the Chichibu mountain range, central Japan, located within a 25-km radius; all but two populations were at altitudes of 1,100-1,400 m. The results indicate the effects of geographic topology on the landscape genetic structure of the populations and should facilitate the development of local-scale strategies to conserve and manage them. Analyses involving 11 nuclear simple sequence repeat loci showed that most populations had similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A mountain ridge is the predominant factor causing genetic barrier for mountain plants (Tsuda et al, 2010;Wei et al, 2013). In the present study, the main genetic breaks detected by BARRIER 2.2 were distributed in the places where the east section of Lesser Khingan and its branch Qinghei Mountains are located, suggesting that the mountains greatly hinder the gene exchange among populations on both sides of the mountains.…”
Section: Roles Of Rivers Mountains and Fragmentationmentioning
confidence: 47%
See 1 more Smart Citation
“…A mountain ridge is the predominant factor causing genetic barrier for mountain plants (Tsuda et al, 2010;Wei et al, 2013). In the present study, the main genetic breaks detected by BARRIER 2.2 were distributed in the places where the east section of Lesser Khingan and its branch Qinghei Mountains are located, suggesting that the mountains greatly hinder the gene exchange among populations on both sides of the mountains.…”
Section: Roles Of Rivers Mountains and Fragmentationmentioning
confidence: 47%
“…For example, rivers, which facilitate movement of individuals and genes across the landscape, are generally recognized as corridors for riparian or aquatic plants (Chen et al, 2012a,b;Yan et al, 2016). On the other hand, mountain ridges as geographical barriers may hinder gene flow and cause genetic differentiation in plants (Tsuda et al, 2010). Fragmentations in habitats may disrupt or reduce gene flow and erode the genetic variation of plants (Werth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by the results of AMOVA, which showed that there was significant differentiation among rivers, whereas no significant differentiation was found among altitudinal zones (Table 6). Mountain ridges have been found as genetic barriers for another wind dispersed tree species, Betula maximowicziana [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mountain ridge is the predominant factor causing limited gene flow and genetic differentiation in mountain plants [6], [23]. As streamside in mountainous areas is always at the bottom of a deep valley, linear distribution patterns constrained by highlands on both sides render populations with sharp boundaries and strong natural fragmentation; such spatial structure hampers gene flow among rivers.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high level of gene flow is resulted from two species-specific traits, including wind pollination and the production of small wind-dispersed samaras (Sato et al 2006;Tsuda et al 2010). …”
Section: Congruence Of Genetic Diversity Between Headwater and Conflumentioning
confidence: 99%